On the Location of Plug-In Relay Devices for Indoor Power Line Communication Environment - Wu, X.; Rong, Yue (IEEE, 2014)
Indoor power line communication (PLC) systems experience high attenuation and frequency-selective channel condition, in addition to different types of colored noises. Its performance is heavily influenced by the length and topology of the in-house power cable wiring. By exploiting the broadcast property of the indoor power grid to each outlet, this paper presents a simple but practical relay-based cooperativecommunication scheme for indoor PLC networks. By plugging a relay device into a third outlet between the transmitter and receiver, reliable signal-to-noise ratio (SNR) can be cooperatively achieved by setting proper system parameters. The condition for the optimal location of the plug-in relay device has been identified. Numerical simulation results show that with the cost of extra relay device, more reliable performance can be obtained with respect to the conventional direct transmission scheme.